Formulation of an Eruption Mitigation Plan for Mount Merapi Based on Settlement Land Suitability in Umbulharjo, Yogyakarta - F.J.R. Putri; Yulfiah Yulfiah (Journal of Applied Sciences, Management and Engineering Technology, 2026)
Umbulharjo sub-district, Kapanewon Cangkringan has experienced an increase in population every year, thereby intensifying the demand for residential land. The area of Umbulharjo sub-district is located within the Mount Merapi Disaster-Prone Area (DPA). Land suitability is an important instrument in mitigation efforts, as it provides an overview of the physical characteristics of the area that influence the level of disaster risk. This study aims to formulate an eruption mitigation plan for Mount Merapi from technical and social perspectives. Residential land suitability analysis was conducted using a quantitative method, namely an overlay technique employing ArcGIS software. The results show that 78.24% of the land is marginally suitable, 21.04% is unsuitable, and less than 1% is suitable for residential use. Relocation emerges as one of the main mitigation strategies to eliminate risk, especially for communities living within disaster-prone zones. However, relocation presents its own implementation challenges, as residents in the study area are unwilling to be relocated, despite the existence of local government policies regulating relocation. Therefore, in addition to focusing on spatial planning, the mitigation plan is also formulated from technical and social aspects, such as enhancing building resilience to earthquakes and volcanic ash, planning evacuation routes, and providing community education, particularly regarding disaster preparedness.